Corporate social and financial performance: Revisiting the role of innovation - Timo Busch; Maximilian Schnippering (Corporate Social Responsibility and Environmental Management, 2022)
R&D intensity has been highlighted as an important factor in analyzing the relationship between corporate social (CSP) and corporate financial performance (CFP). However, the underlying mechanisms of how R&D intensity influences the CSP-CFP relationship have caused a great deal of confusion: first, while controlling for R&D intensity, studies have continued to report ambiguous results and, second, many studies have found R&D intensity to be negatively related to CFP. Motivated by insights from the innovation literature, we revise the functional relationship and examine moderation effects of R&D intensity. Accordingly, we find a u-shaped relationship between R&D intensity and CFP. We conclude that this functional relationship is an essential finding for future CSP-CFP studies in order to avoid misspecifications. Further, we cannot find empirical support for a moderation effect of R&D intensity. Thus, we conclude that R&D intensity and CSP should not be considered to be mutually reinforcing drivers of CFP.
Keywords: 650; corporate financial performance (CFP); corporate social performance (CSP); innovation and sustainability; R&D management